HISTORY OF THE DEVELOPMENT OF ISLAMIC THEOLOGY - Ramadhan, Narendra Jumadil Haikal; Haqi, Muhammad Zainul; Hanafi, Yusuf (CV. Fahr Publishing, 2024)
This study aims to trace the historical development of theology in Islam and identify the factors that influence the emergence of various theological schools in Islam. This research also aims to understand how different theological views affect the way of thinking and lifestyle of Muslims. The research method used is the historical method which includes four stages: heuristics, verification, interpretation, and historiography. The results show that the development of Islamic theology can be divided into three main periods: classical, medieval, and modern. In the classical period, the rational and scientific Sunnatullah theology flourished, resulting in high productivity in various fields. However, in the medieval period, the fatalistic theology of Jabariyah dominated, causing a decline in theological thought. In the modern period, Islamic thinkers such as Sayyid Ahmad Khan, Ismail Raji Al-Faruqi, Muhammad Abduh, and Hasan Hanafi tried to adapt Islamic teachings to the changing times through a rational and contextual approach. They emphasized the importance of ijtihad and reassessment of the language and historical context of classical theology to answer the challenges of modernity. This research contributes to enriching contemporary Islamic studies with in-depth insights into the evolution of theological thought in Islam.